To Teach in a Foreign Land: The Lived Experiences of Non-Immigrant Cultural Exchange Filipino Teachers - Samia, Frances Rowena Mercado; Calaguas, Glenn Medallon (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The study focused on the lived experiences of non-immigrant cultural exchange Filipino teachers in the united states (US). Particularly, the reasons for moving to the US to teach and leaving a permanent position at the philippine department of education (DepEd) were explored. Methodology: A total of eight Filipino teachers currently teaching in the US served as participants in the study. These participants were chosen through the use of purposive and snowball sampling methods, with the following criteria taken into consideration: teachers from the Philippines who moved to the US to teach; DepEd being the previous employer; single; and holder of a J-1 visa. The descriptive phenomenological approach was employed to discover the underlying meanings of the participants’ experiences. Particularly, Collaizi’s descriptive-phenomenological method was used. Main Findings: Through Collaizi’s descriptive-phenomenological method, six themes were identified. These themes were considerations, motivations, preparations, challenges, pleasant experiences, and future outlooks. Novelty/Originality of this study: The study provided insights into the lived experiences of former basic education teachers in the Philippines who opted to work in the US as cultural exchange teachers. The themes identified in the study can serve as guide in better understanding the experiences of these teachers as they venture into the teaching profession in a foreign environment.